The Impact of Accrual Based Investment Ratio and Assets Efficiency Ratio of Fraudulent Financial Reporting - Zatillah, Puteri Maliki Lailatul Fitri Nurid; Primasari, Niken Savitri (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2024)
The decline in the LQ45 index in 2020, which occurred again at the end of 2022 to early 2023, is the background of this research. This study aims to determine the effect of Accrual based investment ratio using variable earnings per share, dividends per share, total share profitability, price earnings ratio and assets efficiency ratio. The population in this study are companies that have been included in the LQ45 index during the 2019-2023 period. The sampling method used was purposive sampling method and obtained 20 companies with a total sample of 100 financial statements which became the object of research. The data analysis method is quantitative analysis using multiple linear regression analysis and hypothesis testing using the SPSS 26 program. The results showed that the variable earnings per share and dividends per share had a significant positive effect on fraudulent financial reporting. While total share profitability and asset efficiency ratio had a significant negative effect on fraudulent financial reporting, the price earnings ratio variable has no effect on fraudulent financial reporting.